Perbedaan Sumpek Antara Wanita dan Pria Penghuni Pemukiman Padat di Kota Yogyakarta - Indra Wahyudi; Riang Gumanti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2014)
This aim of this research was to understand the difference of sumpek between women and men who live in high density area in Yogyakarta, The women ability that is more adaptive on several aspects made the reasearcherformmulateda hypothesis "There is a difference on sumpek between women and men who live in high density place in Yogyakarta, men, tend to feel sumpek or crowded compared to women ". Samples of this research were taken from the highest densely populated area in Yogyakarta, with stratified sampling tecniques. The reasearcher got ¡10 samples which were 52 women and 58 men from kecamatan Pakualaman andDanUrejan. The result showed t (52,58) = -1,198 with p> 0,05. The result showed that there was no significant difference between two groups that were compared, so the hypothesis that was stated, that was a difference on sumpek between women and men who live in high density place in Yogyakarta is rejected.Key words: sumpek, men and women, high density area